The Use Of PjBL In Improving Reading Comprehension of the Eighth Grade at Junior High School - Azizah, Wafiq; Sriati Usman; Maghfirah; Nur Sehang Thamrin (Institut Agama Islam Negeri Palopo, 2025)
This research examines how well eighth-grade students at SMP Negeri 7 Sigi improve their reading comprehension skills through Project-Based Learning (PjBL). Reading comprehension is one of the most important skills for students learning English as a foreign language (EFL). However, the lack of vocabulary, low motivation, and inefficient teaching strategies cause problems for many students. PjBL is used as a student-centered learning strategy to address this issue. This research applied a quasi-experimental approach, with a control group learning conventionally and an experimental group using PjBL. Pre-tests and post-tests were used to gather information about students' reading comprehension development. The average score of the experimental group increased from 34.37 to 49.28, showing a substantial improvement, while the control group increased from 35.82 to 46.38. A p-value of 0.001, which is less than 0.05, was obtained through statistical analysis using an independent sample T-test, indicating that the improvement in the experimental group is statistically significant. This study shows that PjBL can improve students' reading comprehension by encouraging active learning, collaboration, and critical thinking. Based on this, the researchers recommend applying PjBL in English language teaching to create a more engaging and meaningful learning experience. Keywords: Project-Based Learning, Reading Comprehension, Teaching Strategies, Narrative Text